Pharmacokinetics of tetracycline in plasma, synovial fluid and milk using single intravenous and single intravenous regional doses in dairy cattle with papillomatous digital dermatitis - Rodrigues, Celso Antonio [UNESP]; Hussni, Carlos Alberto [UNESP]; Nascimento, Elizabeth de Souza; Esteban, Cláudia; Perri, Sílvia Helena Venturoli (Wiley-Blackwell, 2010)
The purpose of this study was to compare the pharmacokinetics of tetracycline in plasma, synovial fluid, and milk following either a single systemic intravenous (i.v.) injection or a single i.v. regional antibiosis (IVRA) administration of tetracycline hydrochloride to dairy cattle with papillomatous digital dermatitis (PDD). To this end, plasma and synovial fluid tetracycline concentrations were compared with the minimal inhibitory concentration (MIC) values of the major bacteria, which are known to cause digital diseases and thus assess its efficacy in PDD. Residual tetracycline concentrations in milk from cows treated by both methods were also determined. Twelve Holstein cows with various stages of PDD were randomly assigned to two groups of six animals. Group 1 received a single systemic i.v. injection of 10 mg/kg of tetracycline hydrochloride. Group 2 received 1000 mg of tetracycline hydrochloride by IVRA of the affected limb. Blood, synovial fluid and milk samples were taken prior to tetracycline administration (time 0 control), and then at 22, 45 and 82 min, and 2, 3, 4, 6, 8, 12, 24, 48, 72, 96, and 120 h following drug administration. Tetracycline concentrations were determined by high-performance liquid chromatography. Mean tetracycline plasma and milk concentrations in Group 1 were higher than Group 2. The opposite was observed for synovial fluid concentrations. Group 2 synovial fluid concentrations were higher than the MIC value over 24 h for the bacteria most frequently responsible for claw disease. Compared with i.v. administration, IVRA administration of tetracycline produced very high synovial fluid and low plasma and milk concentrations.